Achieving dual-responsive fluorescence switching towards mechanical force and volatile acid vapor based on D-A type diphenylamine functionalized quinoxaline derivatives. (December 2021) - Zhao, Feng; Sun, Ting; Wang, Yu; Zhan, Yong; WenjunYang,
Abstract: New D-A type diphenylamine modified quinoxaline derivatives DPA-DPQ and 2DPA-DPQ have been synthesized by the classical nucleophilic substitution reaction. Two compounds exhibit obvious solvatochromism in different polarities of the solvents. Spectral change and theoretical calculation indicate the presence of D-A structures. Two fluorophores also show interesting dual-stimuli responsive properties. The emission wavelengths and intensities of DPA-DPQ and 2DPA-DPQ can be switched in response to not only external force but also the protonation effect with rapid response times. The dual-response performances endow these molecules with practical applications in stress and acid/base fluorescence sensing. Graphical abstract: Image 1 Highlights: New D-A type diphenylamine modified quinoxaline derivatives DPA-DPQ and 2DPA-DPQ have been synthesized. Two fluorophores show interesting dual-stimuli responsive properties. The films constructed by DPA-DPQ and 2DPA-DPQ act as sensing materials to quantitatively detect acid vapors.